Theo-Anthropocentric Paradigm on Qur’anic Interpretation in the Modern-Industrial Era; A Review of Cultural Interpretation by Cliffort Geertz - Muhammad Rikza Muqtada (Universitas Islam Negeri (UIN) Salatiga, 2023)
This article describes the interpretation of the Qur’an with the theo-anthropocentric paradigm as a solution in responding to the crisis experienced by Muslims in the modern industrial era. The backwardness of Muslims in the current era is more due to their perspective on their religion, which is still within the traditional-agrarian framework of thinking. For this reason, a solution is needed to view interpretation in the modern industrial era. The research method used is descriptive-analytical with the cultural interpretation framework of Cliffort Gertz. The finding is that the perspective of interpretation in the modern-industrial era will always be related to the discourse on the development of Islamic studies, which includes three things; religious texts (Qur'an and Hadith), religion (Islam), and society (Muslims). Through Geertz's conception of cultural interpretation, the Qur’an becomes a symbol of a religious phenomenon that can be understood through the community's social activities. This conception necessitates that the Qur’an is part of that culture and will continue to dialogue and adapt to the changing paradigms of the times. In this context, the interpretation of the Qur’an in the modern-industrial era must apply a theo-anthropocentric paradigm, namely by developing a religious interpretation that is theologically in line with faith in Allah, epistemologically by human experience, and axiologically in favor of human destiny.